Analisis Rasio Cael Untuk Menilai Tingkat Kesehatan Pada Bank Nasional Yang Diakuisis Investor Asing Pada Periode 2019-2021 - Patuteuogo, Rijul; Paramitha, Melvie (Jurnal Etnik: Ekonomi-Teknik, 2023)
Research Analysis of the CAEL Ratio to Assess the Health Level of National Banks Acquired by Foreign Investors in the 2019-2021 Period. This study is entitled "CAEL Ratio Analysis to Assess the Health Level of National Banks Acquired by Foreign Investors in the 2019-2021 Period". CAEL Ratio Analysis is an analysis conducted to assess the health level of banks. The bank's health is the result of qualitative research on various aspects that affect the condition or performance of banks through an assessment of the Capital, Assets, Earnings, and Liquidity factors toward market risk. The purpose of this study was to find out how the CAEL ratio analysis in assessing the health level of the National Bank Owned by Foreign Investors, which has a source of capital from Foreign Investors such as Bank IBK Indonesia, Neo Commerce, KB Bukopin, Permata Bank, Bank Jago, Fama International, KEB Hana , and Seabank. In this study, the data used came from the financial reports for 3 years owned by the bank. The financial reports are processed to produce CAEL ratio calculations. From the calculation of the CAEL ratio, the researcher can determine whether the health level of the bank is classified as "healthy", "quite healthy", "less healthy", and "unhealthy". The results of the CAEL ratio calculation show that of the 8 banks owned by foreign investors, KEB Hana received a healthy predicate for 3 consecutive years.